In Vitro Antioxidant And Cytotoxic Activity Of Leaves And Stem Extracts Of Ecbolium Linneanum - DIPANKAR C; MURUGAN S (International Journal of Pharma and Bio Sciences, 2012)
Ecbolium linneanum is used conventionally to treat various diseases like jaundice, rheumatism and also used as anti-inflammatory agents. Pharmacological properties of the leaf and stem of E. linneanum were evaluated by antioxidant potential and cytotoxic activity. Ethanol, acetone, dichloromethane and petroleum ether extracts of leaf and stem of E. linneanum were prepared to study the total phenolic content, radical scavenging activity, reducing power assay, total antioxidant capacity and cytotoxic by multiple in vitro assays. The total phenolic content, analysed by using Folin- Ciocalteau reagent, varied from 33.3 to 129.00 mg/g dry weight. The results showed that leaf and stem extracts of E. linneanum possesses antioxidant and free radical scavenging properties. Moreover, cytotoxicity was also examined in vitro in HeLa cervical cancer cell line by trypan blue assay and ethanolic extract of leaf exhibited over 80% cell death. This study revealed that the activities observed could be attributed to the presence of some phytochemicals which have been associated with antioxidant and cytotoxic property.